2016
DOI: 10.1007/s00432-016-2192-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of the novel classification of lung adenocarcinoma in patients with stage IB

Abstract: SOL/MIP predominant pattern was predictive for ACT benefit for DFS among invasive lung adenocarcinoma patients in stage IB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…A recent study [33] examined 928 patients with stage IB adenocarcinoma. The overall survival in this cohort was 87% and DFS was 73%.…”
Section: Predominant Pattern and Treatment Decisionsmentioning
confidence: 99%
“…A recent study [33] examined 928 patients with stage IB adenocarcinoma. The overall survival in this cohort was 87% and DFS was 73%.…”
Section: Predominant Pattern and Treatment Decisionsmentioning
confidence: 99%
“…Positron emission tomography (PET) scans were recommended for patients with suspicious hilum or mediastinal lymph node enlargement. The postsurgical surveillance was performed as previously described (19,20): chest CT and neck and upper abdominal ultrasound examinations were performed every 3 months for the first …”
mentioning
confidence: 99%
“…Although several previous studies have reported poor prognosis of solid tumors in stage IB postoperative recovery and suggested ACT for this population, direct evidence regarding the prognosis of solid predominant versus solid non‐predominant tumor types is limited, and no direct proof regarding the effect of ACT in these two groups has been found . Therefore, we believe our results provide important novel insights into the clinical relevance of this treatment.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, the NCCN guidelines have been updated for patients with high risk factors in stage IB adenocarcinoma, such as tumor size > 4 cm, visceral pleural invasion, lymph‐vascular invasion, poorly differentiated tumors, wedge resection, or incomplete lymph node sampling . After publication of the IASLC/ATS/ERS classification, the relationship between pathological subtypes and the prognosis of recurrence has drawn considerable attention . In an American cohort of 240 subjects, Solis et al .…”
Section: Discussionmentioning
confidence: 99%